SISTEM PENDUKUNG KEPUTUSAN KEUANGAN MABNA KHOMIS DI PONDOK PESANTREN PUTRI WALISONGO MENGGUNAKAN METODE MOORA - Islamiyah, Nadiatul; Andriani, Anita; Heru Mujianto , Ahmad; Widoyoningrum, Sri (Fakultas Teknologi Informasi, 2025)
Financial management at the Putri Walisongo Islamic Boarding School, Jombang, includes acquisition, allocation, use of funds, reports, audits and accountability. The system is still manual using ledgers and sharia books for recording, so administrators experience difficulties in managing income, expenses and accounting. To overcome these obstacles, a web-based financial information system using PHP and MySQL was developed. This system applies the MOORA method as decision support for cash replenishment based on frequency of use, total expenditure and remaining budget. The system involves two users, namely the treasurer and supervisor, who can add, change and delete cash data. The data managed includes student information, income, expenses and reports. With this system, financial management becomes easier and more efficient because it is computerized. Keywords:information system ,finance,moora